2015
DOI: 10.1016/j.jascer.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Seeding technique for lowering temperature during synthesis of α-alumina

Abstract: a b s t r a c tThis paper reports a method for producing ␣-Al 2 O 3 at low temperature using a seeding technique. A white product obtained by hydrolyzing aluminum isopropoxide in water at 80 • C was peptized using acetic acid at 80 • C, which transformed the white product to a transparent alumina sol. ␣-Al 2 O 3 particles were added to the alumina sol as seed material; the sol containing ␣-Al 2 O 3 particles was then transformed to an ␣-Al 2 O 3 -seeded alumina gel by drying the sol at room temperature. The no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, low temperature processes for producing ␣-Al 2 O 3 are desired for saving energy and reducing thermal load on the electronic devices during fabrication. In a previous work, we demonstrated that seeding ␣-Al 2 O 3 nanocrystallites into alumina lowered the annealing temperature for crystallization of the alumina to ␣-Al 2 O 3 [16,17]. There was a risk, though, that the alumina might become inhomogeneous with the seeding, which deteriorates its function.…”
Section: Introductionmentioning
confidence: 97%
“…However, low temperature processes for producing ␣-Al 2 O 3 are desired for saving energy and reducing thermal load on the electronic devices during fabrication. In a previous work, we demonstrated that seeding ␣-Al 2 O 3 nanocrystallites into alumina lowered the annealing temperature for crystallization of the alumina to ␣-Al 2 O 3 [16,17]. There was a risk, though, that the alumina might become inhomogeneous with the seeding, which deteriorates its function.…”
Section: Introductionmentioning
confidence: 97%
“…Over the last few decades, many factors affecting the morphology evolution of α-Al 2 O 3 have been summarized, such as precursor type [8], synthesis routes [7,9,10], nucleation seeds [9][10][11][12] and mineralizers [13][14][15]. Among them, researchers have paid lots of attention to different additives because the mineralizer effect could improve α-phase transformation and morphology evolution [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the activation energy barrier of crystalline transformation by adding crystalline seeds during calcination, hence lowering the calcination temperature, has proven to be an effective method for the preparation of α-Al 2 O 3 particles at low temperature. [21][22][23][24][25][26] Kobayashi et al 22 added a small amount of α-Al 2 O 3 seeds to alumina sol and obtained α-Al 2 O 3 particles at less than 1100 • C. Yamamura et al 23 combined hydrothermal and sol-gel methods with α-Al 2 O 3 as seeds, and even reduced the crystallization temperature of α-Al 2 O 3 to 900 • C, but the obtained α-Al 2 O 3 contained some transition-phase alumina. Except for the self-seeding with α-Al 2 O 3 as seeds, some other crystallized materials such as γ-Al 2 O 3 , δ-Al 2 O 3 , and α-Fe 2 O 3 are also used as seed materials.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the activation energy barrier of crystalline transformation by adding crystalline seeds during calcination, hence lowering the calcination temperature, has proven to be an effective method for the preparation of α‐Al 2 O 3 particles at low temperature 21–26 . Kobayashi et al 22 . added a small amount of α‐Al 2 O 3 seeds to alumina sol and obtained α‐Al 2 O 3 particles at less than 1100°C.…”
Section: Introductionmentioning
confidence: 99%